ANALISIS POSTUR KERJA OPERATOR PADA AKTIVITAS PENGAMBILAN FRONT WHEEL DI ASSEMBLING UNIT 2A PT XYZ MENGGUNAKAN METODE REBA - Wijaya, Indra; Setiawan, Setiawan; Purwanto, Cipto (Teknik Industri Unikom, 2026)
The purpose of this study is to evaluate the level of ergonomic risk in the front wheel retrieval activity performed by operators in the assembling unit 2A area of the automotive industry and to propose solutions to reduce the potential occurrence of Musculoskeletal Disorders (MSDs). In this study, the Rapid Entire Body Assessment (REBA) method was used, supported by direct observation, documentation of operator working postures, and interviews. The initial analysis results showed that the activity had a REBA score of 10, which falls into the high-risk category and requires immediate corrective action. The results indicate that the front wheel retrieval process can be assisted by using a hook suspended from an Endo (spring balancer) and moving along a Henderson rail. After implementing the proposed improvement, the REBA score decreased to 3, indicating a low-risk level. These results demonstrate that the use of assistive tools can improve the operator’s working posture, reduce physical workload, and minimize the risk of MSDs. This study contributes to improving work comfort, operator safety, and productivity in the assembling unit production line.